MECHANISMS OF ENZYME ACTION. STRUCTURE OF COENZYMES. ACTIVE SITES OF ENZYMES - Bakayeva Shoira Baxshilloyevna; Achilova Azimabonu Akmalovna; Asadova Ruhsora Avazovna (Western European Studies, 2025)
This paper examines the mechanisms of enzyme action, the structure of their active sites, and the organization of coenzymes. The features of enzyme–substrate interactions, the stages of catalytic processes, and the role of coenzymes in enzymatic reactions are discussed. The biological significance of enzymes and their functions in metabolic processes are also analyzed
Keywords: enzyme; coenzyme; active site; catalysis